The Detection and Surveillance of Asian Citrus Psyllid (Diaphorina citri)—Associated Viruses in Florida Citrus Groves - Britt, Kellee; Gebben, Samantha; Levy, Amit; Al Rwahnih, Maher; Batuman, Ozgur (Frontiers in Plant Science, 2020)
The plant pathogenic bacterium Candidatus Liberibacter asiaticus (CLas), the causal agent of the citrus disease Huanglongbing (HLB), and its insect vector, the Asian citrus psyllid (ACP; Diaphorina citri), have been devastating the Florida citrus industry. To restore the competitive production presence of Florida in the worldwide citrus market, effective and sustainable control of HLB and the ACP needs to be identified. As alternatives for resistance-inducing insecticides, viruses are currently being considered for biological control of the ACP. To identify possible biological control candidates, we conducted one of the most comprehensive surveys of natural ACP populations in major citrus production regions spanning 21 counties in Florida. By optimizing PCRs and RT-PCRs, we were able to successfully detect and monitor the prevalence of five previously identified ACP-associated RNA and DNA viruses throughout Florida citrus groves, which include: Diaphorina citri-associated C virus (DcACV), Diaphorina citri flavi-like virus (DcFLV), Diaphorina citri densovirus (DcDNV), Diaphorina citri reovirus (DcRV), and Diaphorina citri picorna-like virus (DcPLV). Adult and nymph ACP populations from 21 of Florida's major citrus-producing counties were collected each month during approximately 18 consecutive months. RNA extracts used for these viral screens were also regionally combined and subjected to High Throughput Sequencing (HTS) to reveal a more comprehensive picture of known and unknown viruses in Florida ACP populations. We discovered that DcACV was the most prevalent ACP-associated virus throughout nymph and adult ACP populations in Florida, detected in more than 60% of all samples tested, followed by DcPLV and DcFLV. HTS allowed us to identify a novel ACP-associated reo-like virus and a picorna-like virus. The putative reo-like virus, tentatively named Diaphorina citri cimodo-like virus, was later surveyed and detected back in seasonal adult and nymph ACP samples collected in Florida during this study. HTS generated data also revealed that the most abundant virus in Florida ACP populations was Citrus tristeza virus (CTV), which is not an ACP-associated virus, suggesting persistent presence of CTV infection in citrus throughout Florida groves. Collectively, information obtained from our study may be able to help guide the direction of biotechnological pest control efforts involving a number of viruses that were detected for the first time in Florida ACP populations, including two newly identified ACP-associated viruses.